Bioherbicides: revolutionizing weed management for sustainable agriculture in the era of One-health - Taqi Raza; Muhammad Farhan Qadir; Shakeel Imran; Zobia Khatoon; Muhammad Yahya Khan; Mouna Mechri; Waleed Asghar; Muhmmad Ishaq Asif Rehmani; Sergio de los Santos Villalobos; Tooba Mumtaz; Rashid Iqbal (Current Research in Microbial Sciences)
The main objective of agricultural weed management is to increase crop productivity to maintain a delicate balance between food demand and supply for an increasing population and ensure food security globally. Agriculture plays a significant role in the social life and economy of many developed or developing countries. Blind use of chemical herbicides to maximize crop production exerts many negative environmental impacts and develops resistance among the weed biotypes against herbicides, even representing a high risk to the environment and human health. Thus, in the last few years, the research activities of scientists have increased to find alternative weed control methods. Bioherbicides or biological management of weeds is an emerging topic with decent potential for sustainable crop production. Biological management of weeds has numerous positive aspects and advantages over chemical control, such as being highly selective, specific toward targeted weeds, sustainable, and having minimize harmful effect on the main crop, environment, and humans. Several biological agents, such as bacteria, fungi and viruses, also plant extracts and essential oils, have been introduced, and their bioherbicidal potential has been explored in weed management. To develop an effective bioherbicide, specific and complex types of interaction have been developed between targeted weeds and biological agents. Whereas a limited number of bioherbicides have performed successfully under field conditions to control specific weeds, nonetheless, the efficiency of many other bioherbicidal agents is still inadequate due to many reasons, such as formulation, less persistence in the field as well as lack of host-agent interaction. This critical review paper discusses several different biological methods of weed management, their advantages and disadvantages, and the importance of bioherbicides as weed-controlling agents to achieve global sustainable crop production, in the era of One-health.